Situational and Individual Factors Influencing Undergraduate Students’ Willingness to Communicate in English in the UAE - ZAFAR, FARRAH (2024)
This study explores the factors influencing undergraduate students' Willingness to Communicate (WTC) in English within UAE universities' multicultural and multilingual context. Using a mixed-methods approach, data were collected through surveys and interviews with students and teachers. The findings reveal that individual factors such as self-confidence, motivation, and anxiety significantly impact students' WTC, alongside situational factors including classroom environment, group size, and the nature of speaking tasks. Teachers play a crucial role in shaping WTC by creating supportive environments, adjusting instructional methods, and employing strategies that enhance communication, such as personalized feedback and group activities. The research highlights a gap between teachers' perceptions and students' self-reported WTC, particularly in challenging situations, indicating a need for more targeted strategies to build student confidence. This study contributes to understanding WTC in a diverse educational setting and offers practical recommendations for educators to foster effective communication in English language classrooms.